Nitrogen inputs suppress plant diversity by overriding consumer control - Xiaofei Li; Dean E. Pearson; Yvette K. Ortega; Lin Jiang; Shaopeng Wang; Qiang Gao; Deli Wang; Yann Hautier; Zhiwei Zhong (Nature Communications)
Abstract Anthropogenic nitrogen (N) deposition presents a global threat to ecosystem functions. In terrestrial ecosystems, N-deposition is predicted to increase plant productivity but reduce diversity by bolstering dominant plants that suppress subordinate species. However, herbivores are predicted to offset these effects by consuming excess biomass produced by N-deposition. Here, we use a multifactorial field experiment in a grassland ecosystem to investigate the effects of N-addition on top-down control by herbivores and plant diversity. We show that at ambient N, grasshoppers suppress total plant biomass and community dominance sufficiently to increase plant Shannon diversity, indicating top-down control. Without grasshoppers, N-addition increases total plant biomass by promoting the community dominant and suppressing some subordinates as predicted, but it does not affect plant Shannon diversity relative to ambient-N levels. However, with grasshoppers, N-addition eliminates herbivore controls while simultaneously increasing total plant biomass and community dominance, triggering a 21% plant Shannon diversity loss compared to ambient-N conditions. Mechanistically, we find that N-addition disrupts top-down control by reducing herbivore abundance via effects on (1) plant chemistry, which diminishes food quality, and (2) plant architecture, which elevates predatory spider abundance and lethality. Therefore, we show that N-deposition can toggle system controls from top-down to bottom-up, to the detriment of plant diversity.